Probiotics and other adjuvants in allergen-specific immunotherapy for food allergy: a comprehensive review - Mennini, Maurizio; Piccirillo, Marisa; Furio, Silvia; Valitutti, Francesco; Ferretti, Alessandro; Strisciuglio, Caterina; De Filippo, Maria; Parisi, Pasquale; Peroni, Diego Giampietro; Di Nardo, Giovanni; Ferrari, Federica (Frontiers in Allergy, 2024)
This review delves into the potential of manipulating the microbiome to enhance oral tolerance in food allergy, focusing on food allergen-specific immunotherapy (FA-AIT) and the use of adjuvants, with a significant emphasis on probiotics. FA-AIT, including oral (OIT), sublingual (SLIT), and epicutaneous (EPIT) immunotherapy, has shown efficacy in desensitizing patients and achieving sustained unresponsiveness (SU). However, the long-term effectiveness and safety of FA-AIT are still under investigation. Probiotics, particularly strains of Lactobacillus, play a crucial role in enhancing immune tolerance by promoting regulatory T cells (Tregs) and modulating cytokine profiles. These probiotics can induce semi-mature dendritic cells, enhance CD40 expression, inhibit IL-4 and IL-5, and promote IL-10 and TGF-β, thus contributing to mucosal defense and immunological tolerance. Clinical trials combining probiotics with FA-AIT have demonstrated improved desensitization rates and immune tolerance in food-allergic patients. For example, the combination of Lactobacillus rhamnosus with peanut OIT resulted in a significantly higher rate of SU compared to the placebo group, along with notable immune changes such as reduced peanut-specific IgE and increased IgG4 levels. The review also explores other adjuvants in FA-AIT, such as biologic drugs, which target specific immune pathways to improve treatment outcomes. Additionally, nanoparticles and herbal therapies like food allergy herbal formula 2 (FAHF-2) are discussed for their potential to enhance allergen delivery and immunogenicity, reduce adverse events, and improve desensitization. In conclusion, integrating probiotics and other adjuvants into FA-AIT protocols could significantly enhance the safety and efficacy of FA-AIT, leading to better patient outcomes and quality of life.